Milking the Prices: The Role of Asymmetries in the Price Transmission Mechanism for Milk Products in Austria - Octavio Fernández Amador; Josef Baumgartner; Jesús Crespo Cuaresma (Austrian Institute of Economic Research (WIFO), 2010)
We assess empirically the vertical price transmission mechanism between producer and consumer prices of milk products in Austria using monthly data for the period from January 1996 to February 2010. We consider explicitly the existence of asymmetries in the adjustment to the long-run equilibrium using two different types of threshold vector error correction (VEC) models, where an inaction band in the adjustment to the long-run relationship is defined and alternatively where price dynamics differ between periods of increasing and decreasing trends in causal prices. Our results indicate that asymmetries play an important role in the pass-through of prices of milk products in Austria. We provide statistical evidence concerning the fact that the adjustment only tends to take place when deviations from the equilibrium are large enough. Milk, dairy and cheese products and butter tend to remain in positive margins (measured as deviations from the long-run equilibrium) for the retailers' side. The explicit modelling of non-linearities does not improve out-of-sample forecasting performance.
Keywords: 330; Milchpreis; Milchprodukt; Marktmechanismus; Kointegration; Kointegration; Schätzung; Österreich